Comparison of plasma-derived and recombinant von Willebrand factor by atomic force microscopy - Seyfried, Birgit K.; Friedbacher, Gernot; Rottensteiner, Hanspeter; Schwarz, Hans Peter; Ehrlich, Hartmut; Allmaier, Günter; Turecek, Peter L. (Thrombosis and Haemostasis, 2010)
Human plasma protein von Willebrand factor (VWF) is composed of a series of multimers with molecular weights ranging from 600 to 20,000 kDa or even more. Plasma-derived VWF (pdVWF) and recombinant VWF (rVWF) differ in that the ultra-large molecular weight multimer portion present in rVWF is usually missing in pdVWF due to partial cleavage of VWF by the plasma protease ADAMTS13. Here, tapping mode atomic force microscopy (TM-AFM) was used to visualise the shape and size of rVWF and pdVWF. The morphology of the variants of VWF was comparable, containing both globular and stretched domains. Mean chain lengths of the filaments and diameters of the core globular domains were determined and analysed on a statistical basis. About 72% of the pdVWF molecules and 70% of the rVWF molecules were 100–300 nm long. The portion of very long molecules (>300 nm) was only slightly greater in rVWF than in pdVWF (20% vs. 18%). The diameters of the globular core structures were in the range of 12 to 30 nm for both types of VWF. Inspection of a purified rVWF dimer revealed a similar range for the globular domain (14–32 nm). Finally, we demonstrate a dramatic conformational change for rVWF upon exposure to high shear stress, as has been reported for pdVWF. Our TM-AFM data show that the overall structure of rVWF is similar to that of pdVWF and that rVWF will extend its conformation under shear stress, which is required to exert its function in primary haemostasis.
Keywords: von Willebrand factor; recombinant structure; microscopy; atomic force microscopy; shear stress